FROM SERAT CENTHINI TO START-UP COMMUNITY: PEER TEAM-BASED AND PROJECT-BASED LEARNING FOR TRADITIONAL SNACK INNOVATION IN ELEMENTARY SCHOOLS - Bastian, Helmy; Abrianto, Brian Purli; Nafiah (Journal of Intensive Studies on Language, Literature, Art, and Culture, 2025)
This study analyzes the role of Peer Team-Based Learning (PTBL) and Project-Based Learning (PJBL) in fostering entrepreneurial skills and creativity through traditional snack innovations inspired by Serat Centhini among elementary students. Using action research conducted in two cycles, PTBL was applied in cycle 1 and PJBL in cycle 2 with 30 fifth-grade students selected through purposive sampling. Data were collected through observations, questionnaires, product assessments, and documentation, and analyzed using descriptive quantitative methods. The results indicate that PTBL improved collaboration, cultural understanding, and initial entrepreneurial interest, while PJBL further enhanced practical skills, creativity, and entrepreneurial readiness. PJBL proved more effective in increasing students’ confidence and initiative in simple business planning. Overall, combining PTBL and PJBL effectively supports culturally grounded entrepreneurship learning.